The relationship between managers' emotional intelligence and project management decisions - Nuno J. P. Rodrigues; Catarina I. V. Matos (Administrative Sciences, 2024)
Today, effective project management goes beyond technical skills, incorporating an emotional dimension that plays a crucial role in the success and dynamics of teams. Emotional intelligence (EI), which refers to the ability to control emotions-both one's own and those of others-has become essential for good performance in work environments, often surpassing technical skills. This study aims to explore the relationship between managers' emotional intelligence and decision-making in the context of project management. This research was based on an extensive literature review, followed by multiple interviews with project managers. Using semi-structured interviews, it was possible to identify how EI positively influences decision-making and project success. Managers with high levels of EI are more effective in decision-making, communication, conflict resolution, and leadership, resulting in more cohesive and productive teams. EI is a critical factor for success in project management in companies with the same characteristics as this one, providing a collaborative and effective working environment. The results might clearly assess the current state of the relationship between EI in the context of project management and consequent decisions leading to the project's success.
Keywords: 350; emotional intelligence; project management; project management decisions; project success